Cirebon City Gate Design as a Tourism Landmark Based on Nawa Gapura Marga Raja in Pustaka Rajya Rajya I Bhumi Nusantara Manuscript - Fadhly . Abdillah; Iis Purnengsih (Institut Seni Indonesia Yogyakarta, 2026)
Research done on the Cirebon city gate, based on the Nawa Gapura Marga Raja concept in the study of the Rajya Rajya I Bhumi Nusantara Library manuscript, reveals the value and concept of the gate to create prototypes of today’s gates as Cirebon tourism landmarks from throughout Cirebon’s very deep history. Cirebon, with its great historical and cultural tourism potential, could well become a tourist destination in Indonesia. The research uses an inductive qualitative approach to find and understand phenomena from specific historical events, and then elaborate on them with an analysis of Cirebon cultural history carried out through in-depth interviews with the royal family, cultural figures, government officials and Cirebon inhabitants. Literary studies using the ethnography method allow researchers to experience, interpret, and represent society within the concept of culture. Next, the design process is to be carried out using an Architectural Programming approach to create a prototype gate design that will act as a tourism landmark in Cirebon. This research may help provide knowledge about the tourism landmarks of the city of Cirebon based on ancient manuscripts.